2022
DOI: 10.3390/plants11050700
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Pathways Highly Correlated to NUE through a Combined Metabolomics and Transcriptomics Approach in Eggplant

Abstract: Nitrogen (N) fertilization is one of the main inputs to increase crop yield and food production. However, crops utilize only 30–40% of N applied; the remainder is leached into the soil, causing environmental and health damage. In this scenario, the improvement of nitrogen-use efficiency (NUE) will be an essential strategy for sustainable agriculture. Here, we compared two pairs of NUE-contrasting eggplant (Solanum melongena L.) genotypes, employing GC-MS and UPLC-qTOF-MS-based technologies to determine the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…Mauceri et al found that under nitrogen-deficient conditions, the levels of L-aspartic acid and L-asparagine in eggplants increased, and those of particle-bound starch synthase (WAXY) and endonuclease decreased. However, in the present study, we did not observe a significant difference in L-aspartic acid and L-asparagine content [54]. GLUD1_2 is a mitochondrial enzyme that not only catalyzes the synthesis of glutamate from 2-oxoglutarate and ammonia but also catalyzes the reversible oxidative deamination of glutamate into 2-oxoglutarate, which presents a carbon skeleton for the TCA cycle and has a central function in ammonia metabolism [55,56].…”
Section: Discussioncontrasting
confidence: 72%
“…Mauceri et al found that under nitrogen-deficient conditions, the levels of L-aspartic acid and L-asparagine in eggplants increased, and those of particle-bound starch synthase (WAXY) and endonuclease decreased. However, in the present study, we did not observe a significant difference in L-aspartic acid and L-asparagine content [54]. GLUD1_2 is a mitochondrial enzyme that not only catalyzes the synthesis of glutamate from 2-oxoglutarate and ammonia but also catalyzes the reversible oxidative deamination of glutamate into 2-oxoglutarate, which presents a carbon skeleton for the TCA cycle and has a central function in ammonia metabolism [55,56].…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies evaluated NUE by conducting hydroponic culture in different Solanaceae species, including tomato [ 40 , 41 ], potato [ 42 , 43 ], and eggplant [ 36 , 39 ]. Other works investigated NUE using soil cultivation methods [ 31 , 44–46 ] or combining different abiotic stresses [ 47–49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of particular genes involved in secondary metabolites production can be influenced by the level of TCA cycle metabolites, such as acetyl-CoA, succinyl-CoA, and OAA [46]. According to a study, there was a strong correlation between the glyoxylate and dicarboxylate metabolism of two pairs of genotyped eggplants that had different nitrogen usage efficiency in secondary metabolite production [47]. Our study revealed that the effect of mixture treatment altered various metabolic pathways such as the citrate cycle, glyoxylate and dicarboxylate metabolism, and pyruvate metabolism.…”
Section: Discussionmentioning
confidence: 99%